2017
DOI: 10.1080/14397595.2017.1333670
|View full text |Cite
|
Sign up to set email alerts
|

Do exercise habits during middle age affect locomotive syndrome in old age?

Abstract: Participants with LS were less likely to report a regular exercise habit between the ages of 25 and 50 years than participants without LS. Participants who reported regular exercise habits in middle age had better physical function during old age. Regular exercise habits in middle age appear to protect against LS during the older years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…Several studies have demonstrated a relationship between exercise habits and LS among community-dwelling people. [28][29][30] Kota et al 31) reported that home exercise intervention led to improved physical function in communitydwelling elderly individuals. Maruya et al 32) showed the effectiveness of a 6-month exercise program for improving GLFS-25 scores.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a relationship between exercise habits and LS among community-dwelling people. [28][29][30] Kota et al 31) reported that home exercise intervention led to improved physical function in communitydwelling elderly individuals. Maruya et al 32) showed the effectiveness of a 6-month exercise program for improving GLFS-25 scores.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Akune et al reported that exercise habits during middle age were associated with a lower prevalence of sarcopenia, which is one of the main causes of LS. Furthermore, Nishimura et al recently reported that exercise habits during middle age contribute to preventing LS in old age. The current results revealed that UCLA scores in the No‐LS group were significantly greater than those in the LS group, suggesting that lower levels of physical activity can contribute to LS, even in young‐ and middle‐aged adults.…”
Section: Discussionmentioning
confidence: 99%
“…No-LS and LS groups et al 30 recently reported that exercise habits during middle age contribute to preventing LS in old age. The current results revealed that UCLA scores in the No-LS group were significantly greater than those in the LS group, suggesting that lower levels of physical activity can contribute to LS, even in young-and middle-aged adults.…”
Section: T a B L E 4 Characteristics Of Thementioning
confidence: 99%
“…The effects of physical activity and exercise on LS risk have mostly been studied among the general population, using subjects with no regular exercise habits as the control group. Regular exercise habit in middle age has been reported to be an important factor in protection against LS in older years [18]. However, the long-term effects of different levels of intensity, bodily collision, and physical contact during exercise on the risk of LS have not been clarified.…”
Section: Introductionmentioning
confidence: 99%